Textbook Based on Local Wisdom for Learning Text Description in Indonesian Language Subjects for Class IV - Regita Vian Priswanti; Suhartiningsih; Nindya Nurdianasari; Vivi Darmayanti; Trapsila Siwi Hutami (Universitas Pendidikan Ganesha, 2024)
The textbooks in schools still come from student books developed by the government, which are still general in nature. Its means that students do not yet know the local wisdom that exists in Situbondo Regency. This research aims to develop textbooks based on local wisdom. This development research uses the Borg and Gall development model, but its implementation only reaches the eighth stage. The research subjects were fourth grade students at SDN 4 Kendit. Data collection methods in this research include observation, interviews, tests and documentation. The data collection instruments used were observation guidelines, interview sheets, student response questionnaire sheets, documentation sheets, and learning outcomes test sheets. The analytical method used includes descriptive quantitative analysis. Data analysis techniques use, product validation, trials, product effectiveness, and product practicality. The development of textbooks based on local wisdom produces products that are valid, effective and practical. Product validity scores 89% (very decent). The effectiveness of the product is shown by the results of student learning tests which get a relative effectiveness of 100% (high effectiveness). Product practicality received a score of 95.8% (very practical). Based on the data above, it can be concluded that textbooks based on local wisdom are valid, effective and practical to use in implementing learning. The implication is that the products produced in this research have a positive effect on student learning outcomes.